2016
DOI: 10.1038/srep24302
|View full text |Cite
|
Sign up to set email alerts
|

Improved emotional conflict control triggered by the processing priority of negative emotion

Abstract: The prefrontal cortex is responsible for emotional conflict resolution, and this control mechanism is affected by the emotional valence of distracting stimuli. In the present study, we investigated effects of negative and positive stimuli on emotional conflict control using a face-word Stroop task in combination with functional brain imaging. Emotional conflict was absent in the negative face context, in accordance with the null activation observed in areas regarding emotional face processing (fusiform face ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 56 publications
0
13
1
Order By: Relevance
“…For the avoidance comparison between a neutral vs. a happy crowd, we observed greater activations in the bilateral MTG and SFG, STS, PCC, PHC, ACC, mPFC in the left hemisphere. Some of these areas including the MTG, PCC, and ACC are also known to be engaged in emotional conflict resolution, coupled with DLPFC which is responsible for integration of emotional and affective processes 88,89,132 . Thus, this result suggests that choosing a neutral vs. a happy crowd as a relative option to be avoided may engage an additional control mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…For the avoidance comparison between a neutral vs. a happy crowd, we observed greater activations in the bilateral MTG and SFG, STS, PCC, PHC, ACC, mPFC in the left hemisphere. Some of these areas including the MTG, PCC, and ACC are also known to be engaged in emotional conflict resolution, coupled with DLPFC which is responsible for integration of emotional and affective processes 88,89,132 . Thus, this result suggests that choosing a neutral vs. a happy crowd as a relative option to be avoided may engage an additional control mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…Unexpectedly, the reverse effect on N2 amplitudes of fearful faces between congruent and incongruent trials was observed compared to that of happy faces. Some relevant ERP and behavioral studies did not observe the significant differences between congruent trials and incongruent trials in response to fearful faces as that to happy faces (Liu et al, 2013 ; Yang et al, 2016 ). Yang et al ( 2016 ) regarded the disappearance of emotional conflict effect for negative faces were due to the timely resolution on the negative conflicts.…”
Section: Discussionmentioning
confidence: 95%
“…Some relevant ERP and behavioral studies did not observe the significant differences between congruent trials and incongruent trials in response to fearful faces as that to happy faces (Liu et al, 2013 ; Yang et al, 2016 ). Yang et al ( 2016 ) regarded the disappearance of emotional conflict effect for negative faces were due to the timely resolution on the negative conflicts. The current results might further reveal that the conflict monitoring was enhanced when the stimuli only contained fearful faces, and the negative fearful information might narrow one’s view field (Fenske and Eastwood, 2003 ).…”
Section: Discussionmentioning
confidence: 95%
“…Pessoa (2009) noted that according to the dual competition model, the cognition resources required for conflict processing were shared by the processing of negative images. Since most studies on the interaction between emotion and CSEs were conducted in adults (e.g., Albert et al, 2010; van Steenbergen et al, 2010; Padmala et al, 2011; Chechko et al, 2014; Fritz et al, 2015; Yang et al, 2016), little is known about the interplay between the identification of different expressions and CSEs during childhood, particularly in young children. Our results revealed that children had faster RTs and lower error rates for happy target expressions than for fearful expressions, which is consistent with previous findings in adults and young children (Chechko et al, 2014; Liu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%